Mangiferin Alleviates Postpartum Depression–Like Behaviors by Inhibiting MAPK Signaling in Microglia - Yan, Meichen; Bo, Xuena; Zhang, Xinchao; Zhang, Jingdan; Liao, Yajin; Zhang, Haiyan; Cheng, Yong; Guo, Junxia; Cheng, Jinbo (Frontiers in Pharmacology, 2022)
Postpartum depression (PPD), a severe mental health disorder, is closely associated with decreased gonadal hormone levels during the postpartum period. Mangiferin (MGF) possesses a wide range of pharmacological activities, including anti-inflammatory. Growing evidence has suggested that neuroinflammation is involved in the development of depression. However, the role of MGF in the development of PPD is largely unknown. In the present study, by establishing a hormone-simulated pregnancy PPD mouse model, we found that the administration of MGF significantly alleviated PPD-like behaviors. Mechanistically, MGF treatment inhibited microglial activation and neuroinflammation. Moreover, we found that MGF treatment inhibited mitogen-activated protein kinase (MAPK) signaling in vivo and in vitro. Together, these results highlight an important role of MGF in microglial activation and thus give insights into the potential therapeutic strategy for PPD treatment.